AMBN mutations causing hypoplastic amelogenesis imperfecta and Ambn knockout‐NLS‐lacZ knockin mice exhibiting failed amelogenesis and Ambn tissue‐specificity. Issue 9 (11th August 2019) - Liang, Tian; Hu, Yuanyuan; Smith, Charles E.; Richardson, Amelia S; Zhang, Hong; Yang, Jie; Lin, Brent; Wang, Shih‐Kai; Kim, Jung‐Wook; Chun, Yong‐Hee; Simmer, James P.; Hu, Jan C.‐C.
Abstract: Background: Ameloblastin (AMBN) is a secreted matrix protein that is critical for the formation of dental enamel and is enamel‐specific with respect to its essential functions. Biallelic AMBN defects cause non‐syndromic autosomal recessive amelogenesis imperfecta. Homozygous Ambn mutant mice expressing an internally truncated AMBN protein deposit only a soft mineral crust on the surface of dentin. Methods: We characterized a family with hypoplastic amelogenesis imperfecta caused by AMBN compound heterozygous mutations (c.1061T>C; p.Leu354Pro/ c.1340C>T; p.Pro447Leu). We generated and characterized Ambn knockout/NLS‐lacZ ( Ambn lacZ/lacZ ) knockin mice. Results: No AMBN protein was detected using immunohistochemistry in null mice. ß‐galactosidase activity was specific for ameloblasts in incisors and molars, and islands of cells along developing molar roots. Ambn lacZ/lacZ 7‐week incisors and unerupted (D14) first molars showed extreme enamel surface roughness. No abnormalities were observed in dentin mineralization or in nondental tissues. Ameloblasts in the Ambn lacZ/lacZ mice were unable to initiate appositional growth and started to degenerate and deposit ectopic mineral. No layer of initial enamel ribbons formed in the Ambn lacZ/lacZ mice, but pockets of amelogenin accumulated on the dentin surface along the ameloblast distal membrane and within the enamel organ epithelia (EOE). NLS‐lacZ signal was positive in the epididymis and nasal epithelium, but negative in ovary, oviduct, uterus, prostate, seminal vesicles, testis, submandibular salivary gland, kidney, liver, bladder, and bone, even after 15 hr of incubation with X‐gal. Conclusions: Ameloblastin is critical for the initiation of enamel ribbon formation, and its absence results in pathological mineralization within the enamel organ epithelia. Abstract : Compound heterozygous AMBN mutations are shown to cause hypoplastic amelogenesis imperfecta and Ambn knockout/NLS‐lacZ knockin mice are generated and characterized, demonstrating that no enamel ribbons form without ameloblastin and that amelogenin accumulates where the ribbons should have formed.